Upaya dasar pencegahan stunting di Distrik Yaffi, Kabupaten Keerom, Provinsi Papua: Basic Efforts of Stunting Prevention in Yaffi District, Keerom Regency, Papua Province - Girik Allo, Albertus; Tubur , Herman Wafom; Mentansan , George; Yuminarti , Umi; Widati , Agatha Wahyu; Sonbait , Lukas Yowel; Uria , Darmawanto; Rachim , Armansyah; Girik Allo , Caecilia Bintang; Paranoan , Nicea Roona (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT Stunting is a condition where toddlers experience prolonged malnutrition, resulting in growth disturbances manifested by shorter height compared to age standards. Stunting receives significant attention from the government because it not only affects a child's height but can also impact cognitive functions and lead to health problems such as diabetes, high blood pressure, and other health issues. In 2022, stunting in Indonesia reached 22.6%, a figure that remains high compared to the target of the National Medium-Term Development Plan (RPJMN), which is 14%. Papua Province is among the top three provinces with a high prevalence of stunted toddlers, reaching 34.6%. Papua Province consists of several districts, one of which is Keerom District with a prevalence of stunted toddlers at 25.9%. ne of the influencing factors is the community's lack of awareness about stunting, including its symptoms, impacts, and prevention methods. Therefore, a team conducted awareness campaigns through lectures with the assistance of posters/leaflets as media to village chiefs and several community figures in one of the districts in Keerom District, namely Yaffi District. The team conducted the campaign in 7 villages in Yaffi District, namely Yabanda Village, Jifanggri Village, Yuruf Village, Amgotro Village, Fefenumbun Village, Akarinda Village, and Manggoapi Village. The total participants in the campaign were 73 household. Village chiefs and community figures showed great enthusiasm in participating in the campaign and expressed hope that the campaign would continue to reach the broader community. Keywords: Stunting; Malnutrition; Awareness Campaign; Keerom District; Yaffi District ABSTRAK Stunting merupakan kondisi balita kurang gizi dalam jangka waktu yang lama sehingga mengakibatkan gangguan pertumbuhan berupa tinggi badan lebih pendek dari standar usia. Stunting mendapatkan perhatian yang besar dari pemerintah karena stunting tidak hanya berdampak pada tinggi badan anak tetapi dapat berdampak pada kognitif hingga dapat menyebabkan masalah kesehatan seperti diabetes, darah tinggi, dan masalah kesehatan lainnya. Pada tahun 2022, stunting di Indonesia mencapai 22,6%. Angka yang masih tinggi jika dibandingkan dengan target Rencana Pembangunan Jangka Menengah Nasional (RPJMN), yaitu 14%. Provinsi Papua masuk dalam tiga besar provinsi dengan prevalensi balita stunting yang tinggi, yaitu 34,6%. Provinsi Papua terdiri dari beberapa Kabupaten/Kota, salah satunya adalah Kabupaten Keerom yang memiliki prevalensi balita stunting sebesar 25,9%. Salah satu faktor yang memengaruhi adalah ketidaktahuan masyarakat terhadap stunting mulai dari gejala, dampak, dan cara mencegahnya. Oleh karena itu, tim membuat sosialisasi berupa ceramah dengan bantuan poster/leaflet sebagai media kepada kepala kampung dan beberapa tokoh masyarakat pada salah satu distrik di Kabupaten Keerom, yaitu Distrik Yaffi. Tim melakukan sosialisasi pada 7 kampung di Distrik Yaffi, yaitu Kampung Yabanda, Kampung Jifanggri, Kampung Yuruf, Kampung Amgotro, Kampung Fefenumbun, Kampung Akarinda, dan Kampung Manggoapi. Total peserta yang mengikuti sosialisasi adalah 73 rumah tangga. Kepala kampung dan tokoh masyarakat sangat antusias mengikuti sosialisasi dan memberikan harapan bahwa sosialisasi dapat terus dilakukan hingga ketingkat masyakarat. Kata kunci: Stunting; Malnutrisi; Kampanye Kesadaran; Kabupaten Keerom; Distrik Yaffi